Injection Moulding Simulation: The Development of Integral Hinges Test Samples Mould Design via Cadmould 3D-F. - Othman, Mohd Hilmi (Journal of Advanced Mechanical Engineering Applications, 2019)
The objective of this research is to develop an integral hinges test samples mould design via injection moulding simulation. The chosen software was Cadmould 3D-F, used to simulate and analyse the injection moulding parameter setting and defects towards the prepared mould design. The runner size and shape was fixed, same as well for the gate location and number of cavities. The test sample that needed to be developed was a sample with an integral hinge at the middle of the injected mould article. Polypropylene PPC 8780 (Total Petrochemical) was chosen as the reference material. SolidWorks was chosen as the solid modelling computer aided design software to prepare the design. This design was then converted into the stereolithography (STL) format. Cadmould 3D-F injection moulding simulation software was used as the computed added engineering analysis tools. Parameters such as temperature and time was monitored. The defects such as sink marks, volumetric shrinkage, warpage, weld lines, and air traps were observed. The results show that the mould design had produced 232Â°C temperature and 0.179 s time when the molten polymer was completely filled. It also produced several defects such as 0.882 % of volume shrinkage and 0.025 mm of warpage. Some sink marks occurred at the above part of the hinge, with 1 weld line and 9 air traps were also detected after simulation. The conclusion of this finding is, the simulation could assist the mould designer to prepare necessary countermeasures in the actual process, and to prepare a better mould with minimum alteration/repair and accelerating setup/preparation time. Hence, the time and cost of a mould could be reduced, especially for new mould design for integral hinge products.